The ANALYSIS OF ACTUAL DRUG INTERACTIONS IN THE TREATMENT OF INPATIBLE GASTRITIS PATIENTS AT RSUD X - Oktaviani, Nadila; Alifiar, Ilham; Nuryadin Zain, Dichy (JFL : Jurnal Farmasi Lampung, 2023)
Gastritis is a health problem with a high prevalence in society. Gastritis is a digestive tract disorder that has problems with damage to the gastric mucosa. Drug interaction events occur when the effect of a drug changes due to the presence of another drug. The purpose of this study was to describe the actual incidence of drug interactions in the treatment of inpatients with gastritis at RSUD X. This research was conducted at RSUD X as an observational study with a cross-sectional study design which was carried out prospectively while the patient was undergoing treatment at the hospital during the period January-April 2023. The sample was collected using a consecutive sampling technique and a total of 64 patients who met the inclusion criteria were obtained. The research results obtained from 22 cases of potential drug interactions found actual drug interaction events in the drug combination between Potassium Chloride (KSR) and Hyoscyamine which provides a synergistic or additive pharmacodynamic interaction because it can benefit patients with increased potassium levels from the therapy. Keywords: Gastritis, Aktual Drug Interaction